The Paleoarchean and Mesoarchean TTGs of the western Azov area, the Ukrainian Shield - Artemenko, G.V.; Shumlyanskyy, L.V. (Reports of the National Academy of Sciences of Ukraine, 2021)
A large anticline structure occurs in the western part of the Azov Domain of the Ukrainian Shield. It is composed of rocks of the Mesoarchean (3.2-3.0 Ga) granite-greenstone association and relics of an older basement. The anticline is divided into two parts by the Bilotserkivka structure of sub-latitudinal strike. The northern part includes the Huliaipole and Remivka blocks, and the southern part comprises the Saltycha anticline. The U-Pb age of plagiogneisses of the Lantsevo anticline of the Bilotserkivka structure is 3299 ± 11 Ma. In terms of geochemical characteristics, they correspond to TTGs. In the western part of the Bilotserkivka structure, we previously identified quartz diorites having an age of 3297 ± 22 Ma. These data show that the Bilotserkivka structure represents an ancient basement. Dislocated trondhjemites were studied in the Ivanivka area at the eastern part of the Saltycha anticline. They contain numerous relics of heavily altered amphibolites. The U-Pb age of zircons from trondhjemite is 3013 ± 15 Ma. These rocks are of the same age as TTGs of the Shevchenko Complex cutting through the sedimentary- volcanogenic rocks of the greenstone structures of the Azov Domain. They share age and geochemical characteristics with biotite and amphibole-biotite gneisses of the “Kainkulak beds” in the Zrazkove village located at the Mokra Konka river (3.1-3.0 Ga) and with biotite gneisses in the lower reaches of the Kainkulak river (2.92 Ga). Thus, gneisses of the “Kainkulak beds” actually represent the Mesoarchean TTGs of the Shevchenko Complex, transformed in the Paleoproterozoic time due to the dislocation metamorphism. The late Paleoarchean (3.3 Ga) tonalites are known in the West Azov and KMA domains; they probably also occur in the basement of the Middle Dnieper domains, where detrital zircons of this age have been reported. These data allow us to assume the existence of a large Late Paleoarchean (3.3 Ga) protocraton, in which the Mesoarchean (3.2-3.0 Ga) greenstone belts and TTGs of the eastern part of the Ukrainian Shield and the KMA Domain were formed.